An Assessment of the Authorization to Sell Veterinary Pharmaceuticals in terms of the Veterinary Profession: III. Relationship between the Authorization to Sell Pharmaceuticals and Residues - Ozen, Abdullah; Yuksel, Erhan; Dogan, Ozlem (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
The present study was conducted to determine the opinions of private veterinary practitioners on the issue of residues in food of animal origin. For this purpose, data was collected from 400 private veterinary practitioners by means of a questionnaire. The analysis of the data demonstrated the occurrence of a high level of vaccine sales at veterinary clinics, 67.3% of participants having the opinion that food of animal origin contained residues, the inadequate sensitivity of veterinarians and animal owners to the withdrawal periods of pharmaceuticals; the major reasons of increase in residues being uncontrolled use of pharmaceuticals and uncontrolled sales of pharmaceuticals; the major reasons of uncontrolled use of pharmaceuticals being sales of pharmaceuticals without performing clinical examination and sales of pharmaceuticals without any prescription. Participants shared the opinion that animal owners were responsible in the first place and veterinarians were responsible in the second place for the increase in residues.
Veteriner İlaçları satış yetkisinin veteriner hekimli?i açısından de?erlendirilmesi: III. İlaç satış yetkisi ile kalıntılar arasındaki İlişki
Keywords: Food of animal origin; Drug residue; Veterinary practitioners